Targeting the Metastatic Bone Microenvironment by MicroRNAs - Haider, Marie-Therese; Taipaleenmäki, Hanna (Frontiers in Endocrinology, 2018)
Bone metastases are a common and devastating feature of late-stage breast cancer. Metastatic bone disease is a consequence of disturbed bone remodeling due to pathological interactions between cancer cells and the bone microenvironment (BME). In the BME, breast cancer cells severely alter the balanced bone formation and bone resorption driven by osteoblasts and osteoclasts. The complex cellular cross-talk in the BME is governed by secreted molecules, signaling pathways and epigenetic cues including non-coding RNAs. MicroRNAs (miRNAs) are small non-coding RNAs that reduce protein abundance and regulate several biological processes including bone remodeling. Under pathological conditions, abnormal miRNA signaling contributes to the progression of diseases such as bone metastasis. Recently miRNAs have been demonstrated to regulate several key drivers of bone metastasis. Furthermore, miRNAs are implicated as important regulators of cellular interactions within the metastatic BME. As a consequence, targeting the BME by miRNA delivery or antagonism has been reported to limit disease progression in experimental and pre-clinical conditions positioning miRNAs as emerging novel therapeutic tools in metastatic bone disease. This review will summarize our current understanding on the composition and function of the metastatic BME and discuss the recent advances how miRNAs can modulate pathological interactions in the bone environment.